Plasma Synthesis of Polymer‐Capped Dye‐Sensitised Anatase Nanopowders for Visible‐Light‐Driven Hydrogen Evolution. Issue 1 (26th November 2012) - Kruth, Angela; Hansen, Sven; Beweries, Torsten; Brüser, Volker; Weltmann, Klaus‐Dieter
Abstract Visible‐light‐driven photocatalysis is currently attracting a great deal of attention because of its potential application in solar water splitting. However, the development of efficient and durable catalyst systems is still a challenging problem. In Ru dye‐sensitised TiO2 nanopowders, catalyst performances are found to decline as a result of poor bonding of the dye molecule to the TiO2 surface and subsequent detachment and self‐aggregation of the dye. Our strategy to improve the stability of the dye–TiO2 interface is the encapsulation of the dye/TiO2 assembly in an amino‐group‐containing polyallylamine layer anchored to TiO2. A low‐pressure pulsed microwave discharge plasma polymerization process was employed to coat a commercial anatase nanopowder with a thin polyallylamine layer to nanoconfine the adsorbed dye molecules. Electron microscopy and UV/Vis spectroscopy was carried out to characterise the resulting encapsulated nanostructures. The long‐term stability of the new nanomaterial as the photoactive component of a water reduction catalyst system for H2 evolution investigated in a slurry reactor under visible‐light irradiation showed stable evolution rates over a period of several days.